2022
DOI: 10.1109/temc.2022.3147471
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Time Diversity Against Multiharmonic Electromagnetic Disturbances Under Reverberation Conditions: An Overview of Fault Mechanisms

Abstract: In this paper, time diversity is used as an electromagnetic resilience technique in a Triple Modular Redundant (TMR) communication channel that is subjected to a multiharmonic electromagnetic disturbance under semi-reverberant environments. The study is carried out in light of new Elec-troMagnetic Interference (EMI) condition monitoring definitions which provide a better insight into the actual state of the system. An explanation of the different fault mechanisms based on the new definitions is provided for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This paper relies on an in-house developed simulation framework that combines the paper of Hill [21], Magdowski et al [22], and Vanhee et al [23]. Different studies, as performed by [24], [25], use and extensively describe this framework. This section will shortly recapitulate this framework, which performs a Monte-Carlo simulation of single or multifrequency continuous wave disturbances, which are incident to a device-under-test (DUT), in this case a Printed Circuit Board (PCB).…”
Section: Fig 1: Simulation Framework Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…This paper relies on an in-house developed simulation framework that combines the paper of Hill [21], Magdowski et al [22], and Vanhee et al [23]. Different studies, as performed by [24], [25], use and extensively describe this framework. This section will shortly recapitulate this framework, which performs a Monte-Carlo simulation of single or multifrequency continuous wave disturbances, which are incident to a device-under-test (DUT), in this case a Printed Circuit Board (PCB).…”
Section: Fig 1: Simulation Framework Outlinementioning
confidence: 99%
“…Figure 4 shows the response of the number of faults as a function of the SIR for a reverberation wave of f EMI = 500 MHz and f BIT = 350 MHz. The algorithm for computation of SIR is explained in [25]. To calculate these probabilities, a large number of codewords are sent through the simulation framework, and the Hamming code is applied to the received codewords.…”
Section: B Em Condition Assessmentmentioning
confidence: 99%
“…Similarly, in [16] it was shown that the 3 rd harmonic component of f Bit was responsible for the first occurring CFNs. Furthermore, in [17], it was shown that the time diverse TMR setup leads to increasing number of CFNs at low SIR values. As this algorithm won't be affected by the 3 rd harmonic homopolar component, this technique is likely to perform better in a multi-harmonic reverberation environment.…”
Section: Performance Limitation Of the Algorithmmentioning
confidence: 99%
“…electromagnetically diverse redundant channels in order to cope with the systematic and common cause effects of EMI. Some of the ways of realizing this diversity is either by varying the bit delays of the transmitted bit stream (time diversity) [3], [17], or the data rate (frequency diversity) [4], or the spatial orientation of traces (spatial diversity) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation